2006
DOI: 10.1159/000092463
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Therapy of Persistent Cloaca: A Case Report

Abstract: Persistent cloaca is a rare abnormality that occurs only in females and is characterized by a direct communication between the gastrointestinal, urinary, and genital structures resulting in a single perineal opening. A case with massive ascites, two cystic structures arising from the fetal pelvis, bilateral hydroureters, calcified meconium, and cardiac anomalies, in which this condition was diagnosed prenatally is presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As urine accumulates in the vagina, a large hydrocolpos could develop. Urine containing a meconium component escapes from hydrocolpos via the fallopian tubes into the peritoneal cavity and causes intrauterine peritonitis [4,5,[11][12][13][14]. In a rare case, Stephenson et al [3] reported a case of MP associated with cloacal malformation and perforated hydrocolpos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As urine accumulates in the vagina, a large hydrocolpos could develop. Urine containing a meconium component escapes from hydrocolpos via the fallopian tubes into the peritoneal cavity and causes intrauterine peritonitis [4,5,[11][12][13][14]. In a rare case, Stephenson et al [3] reported a case of MP associated with cloacal malformation and perforated hydrocolpos.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, MP is complicated with an intestinal obstruction, such as intestinal atresia and meconium ileus. Several pediatric surgeons have described patients with a cloacal anomaly showing intraperitoneal calcification or a dense plastic peritonitis associated with hydrometrocolpos or hydrosalpinx [2][3][4][5][6].…”
mentioning
confidence: 99%
“…[181014] MRI provides high-quality fetal images, regardless of maternal or fetal position or the presence of oligohydramnios. Fetal MRI helps in better anatomical localization of the cloacal anomalies by delineating the communication between the cyst, gastrointestinal tract, and ureter.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some reported cases that presented with persistent fetal ascites. They are often accompanied by oligohydramnios and have an unfavorable course [4,5] . In one case, aberrant drainage of urine through a transverse colostomy continued postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variety affects prenatal ultrasonographic findings, which include fetal ascites, intrapelvic cysts, a poorly visualized fetal bladder, bilateral hydronephrosis and oligohydramnios [1,3] . Of these, the most frequent finding seems to be intrapelvic cysts [4] . These cysts correspond to hydrocolpos, i.e.…”
mentioning
confidence: 99%